(untitled) (Bangladesh Journal of Pharmacology, 2023)
In this study, guanine-modified glassy carbon electrode sensor was developed for the determination of paracetamol. The use of overdose continuously for a long time, its metabolites accumulate and affect the kidneys and liver. Therefore, the detection of paracetamol is of great significance. Differential pulse voltammetry and cyclic voltammetry techniques were employed to analyze the behavior of paracetamol in 0.1 M Britton-Robinson buffer solution of pH 5.0 on guanine-modified electrode. Guanine-modified glassy carbon electrode showed good linear response in the concentration range from 0.5 mM to 10 μM for quantitative determination of paracetamol with lower limit of detection of 0.9 µM.